W KWESTII POCZĄTKÓW WCZESNEGO ŚREDNIOWIECZA W REJONIE NIECKI JEZIOR BNIŃSKICH - Machajewski, Henryk (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
The development of archaeological research justifies the need for re-appraising previous conclusions. In the case of the Bnin Lakes Basin (Wielkopolska), the research pertains to the settlement at the early stage of the early Middle Ages. Human settlement developed dynamically at phase B of the early Middle Ages. To date, settlement from phase A has not been discovered in the Basin. The same holds true for the basin of the central river Warta.